SVC obstruction and stridor relieved by nasogastric tube insertion - Molena, Emma J. (J Surg Case Rep, 2016)
Achalasia is an idiopathic motility disorder of the oesophagus of increasing incidence. It is characterized by aperistalsis of the lower oesophagus and failure of relaxation of the lower oesophageal sphincter. Patients classically present with chronic symptoms of dysphagia, chest pain, weight loss and regurgitation, and they commonly suffer pulmonary complications such as recurrent microaspiration of static, retained food contents of the upper oesophagus. However, it has also been described, uncommonly, to present with megaoesophagus and secondary tracheal compression. We present a case of megaoesophagus secondary to achalasia which presented with stridor and signs of acute superior vena caval obstruction.